Data for Production of negative-emission biomethane by twin double-bed pressure swing adsorption with tail gas sequestration - Golmakani, Ayub; Nabavi, Seyed Ali; Manovic, Vasilije (Cranfield University, 2020)
the experimental results for adsorption capacity of CO2 and CH4 on polymeric porous adsorbent (PPB) as well as dynamic breakthrough measurements have been provided.
Keywords: Biogas Upgrading; pressure swing adsorption; PSA; Biomethane; negative-emission technologies; carbon sequestration processes; Carbon Capture Engineering (excl. Sequestration); Chemical Engineering Design; Environmental Engineering Design